Osteoblast autophagy in glucocorticoid‐induced osteoporosis. Issue 4 (11th November 2018) - Wang, Lufei; Heckmann, Bradlee L.; Yang, Xianrui; Long, Hu
Abstract: Administration of glucocorticoids is an effective strategy for treating many inflammatory and autoimmune diseases. However, glucocorticoid treatment can have adverse effects on bone, leading to glucocorticoid‐induced osteoporosis (GIO), the most common form of secondary osteoporosis. Although the pathogenesis of GIO has been studied for decades, over the past ten years the autophagy machinery has been implicated as a novel mechanism. Autophagy in osteoblasts, osteocytes, and osteoclasts plays a critical role in the maintenance of bone homeostasis. Herein, we specifically discuss how osteoblast autophagy responds to glucocorticoids and its role in the development of GIO. Abstract : Although the pathogenesis of glucocorticoid‐induced osteoporosis (GIO) has been studied for decades, over the past ten years the autophagy machinery has been implicated as a novel mechanism. Autophagy in osteoblasts, osteocytes, and osteoclasts plays a critical role in the maintenance of bone homeostasis. Herein, we specifically discuss how osteoblast autophagy responds to glucocorticoids and its role in the development of GIO.